Efficient influenza A virus production in high cell density using the novel porcine suspension cell line PBG.PK2.1. Issue 47 (8th November 2019) - Gränicher, Gwendal; Coronel, Juliana; Pralow, Alexander; Marichal-Gallardo, Pavel; Wolff, Michael; Rapp, Erdmann; Karlas, Alexander; Sandig, Volker; Genzel, Yvonne; Reichl, Udo
Abstract: Seasonal and pandemic influenza respiratory infections are still a major public health issue. Vaccination is the most efficient way to prevent influenza infection. One option to produce influenza vaccines is cell-culture based virus propagation. Different host cell lines, such as MDCK, Vero, AGE1.CR or PER.C6 cells have been shown to be a good substrate for influenza virus production. With respect to the ease of scale-up, suspension cells should be preferred over adherent cells. Ideally, they should replicate different influenza virus strains with high cell-specific yields. Evaluation of new cell lines and further development of processes is of considerable interest, as this increases the number of options regarding the design of manufacturing processes, flexibility of vaccine production and efficiency. Here, PBG.PK2.1, a new mammalian cell line that was developed by ProBioGen AG (Germany) for virus production is presented. The cells derived from immortal porcine kidney cells were previously adapted to growth in suspension in a chemically-defined medium. Influenza virus production was improved after virus adaptation to PBG.PK2.1 cells and optimization of infection conditions, namely multiplicity of infection and trypsin concentration. Hemagglutinin titers up to 3.24 log10 (HA units/100 µL) were obtained in fed-batch mode in bioreactors (700 mL working volume). Evaluation of virus propagation in high cell density culture using a hollow-fiber based system (ATF2) demonstrated promising performance: Cell concentrations of up to 50 × 10 6 cells/mL with viabilities exceeding 95%, and a maximum HA titer of 3.93 log10 (HA units/100 µL). Analysis of glycosylation of the viral HA antigen expressed showed clear differences compared to HA produced in MDCK or Vero cell lines. With an average cell-specific productivity of 5000 virions/cell, we believe that PBG.PK2.1 cells are a very promising candidate to be considered for next-generation influenza virus vaccine production.